We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
303
13
avatar+1125 

The focus of a parabola is  (−3,−5) . The directrix of the parabola is y=2

.

What is the equation of the parabola?

y=−1/28(x−3/2)^2−3

 

y=−1/28(x+3)^2+3/2

 

y=−1/14(x−3/2)^2+3

 

y=−1/14(x+3)^2−3/2

 

I am thinking it is D

 Feb 6, 2019
 #1
avatar+102947 
+3

The y coordinate of the focus is below the directrix.....thus....this turns downward

 

Find the vertex =  ( -3 , (-5 + 2)/2 ) =  (-3, -3/2)

 

Find p  ..... l -3/2 -  - 5 l  = l  5 - 3/2 l  = [ 10/2 - 3/2 l  =  7/2

 

So.....we have the form

 

-4p(y - k) = (x - h)^2

 

-4(7/2)(y - -3/2) = (x - - 3)^2      simplify

 

-14 ( y + 3/2) = (x + 3)^2             mutiply both sides by -1/14

 

y + 3/2 = -(1/14) ( x + 3)^2        subtract 3/2 from both sides

 

y =  -(1/14)(x + 3)^2 - 3/2

 

Looks like you are correct, jenny  !!!

 

 

cool cool cool

 Feb 6, 2019
edited by CPhill  Feb 6, 2019
 #3
avatar+1125 
+1

From your explantation in the other question it really helped ! Thank you

jjennylove  Feb 6, 2019
 #4
avatar+102947 
+2

OK....

 

 

cool cool cool

CPhill  Feb 6, 2019
 #5
avatar+1125 
+1

The one where you went over each step more in depth

jjennylove  Feb 6, 2019
 #6
avatar+1125 
0

The one above is the steps I took as well thank you .

jjennylove  Feb 6, 2019
 #2
avatar+1125 
+1

this one if you can also

 

The directrix of a parabola is y=−8 . The focus of the parabola is  (−2,−6)

.

What is the equation of the parabola?

y=−1/8(x+2)^2+7

 

y=1/4(x+2)^2−7

 

y=1/8(x−2)^2−7

 

y=−1/4(x−2)^2−7

 

i think it is option 2

 Feb 6, 2019
 #7
avatar+102947 
+2

Second one.....the dirctrix is below the focus....this turns upward

 

Vertex    ( -2 ,  (-6 - 8)/2 )  = (-6, -14/2)  = (-2, -7)    = (h, k)

 

"p" =  l -7 - - 6 l =   l -1 l   =   1

 

We have the form

 

4p(y - h ) =  (x - k)^2

 

4(1) ( y - - 7) =  ( x - - 2)^2

 

4 (y + 7) = ( x + 2)^2            multiply both sides by 1/4

 

y + 7 =  (1/4) ( x + 2)^2       subtract 7 from both sides

 

y =  (1/4)(x + 2)^2 - 7

 

Looks good  !!!

 

 

 

 

cool cool cool

CPhill  Feb 6, 2019
 #8
avatar+1125 
+1

I have this one and jsut 1  more if can double check for me I understand if you cant

 


The directrix of a parabola is the line y=7 . The focus of the parabola is (2,3)

.

What is the equation of the parabola?

y=−1/8(x−2)^2−5

 

y=−1/8(x−2)^2+5

 

y=1/8(x−2)^2+5

 

y=1/8(x−2)^2−5

 

i think it is option c

jjennylove  Feb 6, 2019
edited by jjennylove  Feb 6, 2019
 #9
avatar+102947 
+2

The directrix of a parabola is the line y=7 . The focus of the parabola is (2,3)

 

Remember jenny....if the y coordinate of the focus is less than the directrix....the parabola turns downward

 

Vertex     ( 2,  (3+7)/2)  = (2, 10/2) = ( 2, 5)  = (h, k)

 

"p"  =  l  5 - 3 l = l 2 l = 2

 

We have the form

 

-4p(y - k) = (x - h)^2

 

-4(2) ( y - 5) = ( x - 2)^2

 

-8 ( y - 5) = ( x - 2)^2        divide both sides by -1/8

 

y - 5 =  (-1/8)( x - 2)^2

 

y = -(1/8) ( x - 2)^2 + 5

 

 

 

cool cool cool

CPhill  Feb 6, 2019
 #10
avatar+1125 
+1

If you can check this last one since I am worried because I did not get that other one correct

The focus of a parabola is (0,−2) . The directrix of the parabola is the line y=−3

.

What is the equation of the parabola?

y=−1/2x^2−52

 

y=1/2x^2−52

 

y=1/4x^2−2

 

y=−1/4x^2+2

 

i think it would be option B

jjennylove  Feb 6, 2019
 #11
avatar+1125 
+1

oh okay I see where I made my mistake, I have to watch out for whether it goes downward or upward

jjennylove  Feb 6, 2019
 #12
avatar+102947 
+3

The focus of a parabola is (0,−2) . The directrix of the parabola is the line y=−3

 

The y coordinate of the focus is > the y value of the directrix....thus this opens upward

 

Vertex    ( 0, (-3 +   -2) /2 )   =   ( 0,  -5/2)   =  (h, k)

 

"p"  =   l  -5/2 - - 2 l  =  l  - 5/2 + 2 l  =   l -5/2 + 4/2 l  =  l -1/2  l = 1/2

 

The form is

 

4p ( y - k) = ( x - h)^2

 

4(1/2) ( y -  - 5/2) = (x - 0)^2

 

2(y + 5/2) = x^2        multiply both sides by  1/2

 

y + 5/2  =  (1/2)x^2

 

y = (1/2)x^2  - 5/2

 Feb 6, 2019
 #13
avatar+1125 
+1

THANK YOU!! This all helped so much smiley

jjennylove  Feb 6, 2019

34 Online Users

avatar
avatar
avatar